The Effectiveness of Individual and Environmental Infection Control Measures in Reducing the Transmission of Mycobacterium tuberculosis: A Systematic Review. (5th June 2020) - Fox, Greg J; Redwood, Lisa; Chang, Vicky; Ho, Jennifer
Abstract: Background: Transmission of Mycobacterium tuberculosis in healthcare settings is a preventable driver of the global tuberculosis epidemic. We aimed to assess the evidence for infection control interventions, including cough etiquette, engineering and personal respiratory protection measures, to prevent transmission of M. tuberculosis in healthcare settings. Methods: Three independent systematic reviews were performed using 6 databases and clinical trials websites. Randomized trials, cohort studies, before-after studies, and case-control studies were included. Searches were performed for controlled studies evaluating respiratory hygiene, engineering, and personal respiratory protection measures. Outcome measures included the incidence of tuberculosis infection and disease. Studies involving transmission to either humans or animals were included. Results: Evaluation of respiratory hygiene and cough etiquette interventions identified 4 human studies, with 22 855 participants, and 1 guinea pig study. Studies in humans evaluated the effects of multiple concurrent interventions. Patient use of surgical masks reduced infection by 14.8%, and tuberculosis disease was reduced by between 0.5% and 28.9%. Engineering and environmental interventions were evaluated in 10 studies of humans, including 31 776 human participants, and 2 guinea pig studies. Mechanical ventilation was associated with between 2.9% and 14% less infection. Nine studies of personal respiratory protection were included, including 33 913 participants. Infection was reduced by between 0% and 14.8% in studies where particulate respirators were used. The quality of included studies was assessed as low. Conclusions: Respiratory hygiene, engineering, and environmental infection controls and personal respiratory protection interventions were associated with reduced transmission of M. tuberculosis and reduced tuberculosis disease in healthcare settings. Abstract : Respiratory hygiene, engineering, and environmental infection controls and personal respiratory protection interventions are associated with reduced transmission of M. tuberculosis and reduced tuberculosis disease in healthcare settings. Most studies included in this systematic review evaluated the effect of multiple concurrent interventions.